DEMOCRACY UNDER THREAT: THE POLITICS OF CORRUPTION AND PARTY FINANCING SYSTEM IN INDONESIA - Tambunan, Derwin (Journal of Social Political Sciences, 2021)
After Soeharto's authoritarian regime had ended in 1998, Indonesia has successfully been transformed into one of the world's largest democratic nations. However, Indonesia still faces enormous challenges to eradicating corruption; corruption is still ubiquitous and entrenched in governments and political parties. This study argues that the primary reasons for this apparent paradox are the politics of corruption and the dysfunction of the party finance system underpinning the illicit campaign financing system. This research also claims that the deficiency of the party finance system is not accidental; it is intentionally designed and perpetuated by the elites who prefer the illicit finance system since this system allows them to penetrate the state's assets, creating privileged business opportunities and reserving political advantages. The elites minority overpower political parties and establish politics-business networks to perpetuate their status quo and dominance in politics and economy. The dysfunction of the party financing system has also caused parties to remarkably relied on financial support from conglomerates; this situation engenders politics and 'black' business empires networks and oligarchisation. Further, business and political parties maintain their access to the state's resources by becoming part of electoral democracy, assuming political office or lobbying societal organisations, and taking control over economic actions and election campaigns that undermine Indonesia's democracy system. To substantiate the arguments in this study, the researcher uses the literature study and secondary data sources to support the arguments